Prevalence of Dengue, Chikungunya and Zika Viruses in Blood Donors in the State of Pará, Northern Brazil: 2018–2020 - Leticia Martins Lamarão; Angelita Silva Miranda Corrêa; Renata Bezerra Hermes de Castro; Carlos Eduardo de Melo Amaral; Patricia Danin Jordão Monteiro; Mauricio Koury Palmeira; Luane Nascimento Lopes; Angela Neves Oliveira; Maria Salete Maciel de Lima; Caroline Aquino Moreira-Nunes; Rommel Rodríguez Burbano (Medicina, 2022)
Arboviruses have been reported over the years as constant threats to blood transfusion recipients, given the high occurrence of asymptomatic cases and the fact that the presence of viremia precedes the onset of symptoms, making it possible that infected blood from donors act as a source of dissemination. This work aims to identify the prevalence of dengue virus (DENV), Zika virus (ZIKV) and Chikungunya virus (CHIKV) infection in blood donors during epidemic and non-epidemic periods; classify the donor as symptomatic or asymptomatic; and verify the need to include DENV, CHIKV and ZIKV in the nucleic acid test (NAT) platform in northern Brazil. We investigated 36,133 thousand donations in two years of collection in Northern Brazil. One donor was positive for DENV and one for CHIKV (0.002% prevalence). As the prevalence for arboviruses was low in this study, it would not justify the individual screening of samples from donors in a blood bank. Thus, DENV- and CHIKV-positive samples were simulated in different amounts of sample pools, and both were safely detected by molecular biology even in a pool of 14 samples, which would meet the need to include these three viruses in the routine of blood centers in endemic countries such as Brazil.